Correlation between oil Content and Yield of Some early Maturing Soybean (GLYCINE MAX (L.)MERILL) Genotypes in Keffi, Nasarawa State - Adetokunbo, ADESHINA Dolapo; Esla, ABIMIKU Sunday; Esther, INEGBEDION; Glory, ONONOKPONO Eneotte; Ebun, ADEBOYE Seyi (International Journal of Environment, Agriculture and Biotechnology, 2019)
Soybean meals and oils are very essential for human and animal health. Six varieties of Soybeans were evaluated to determine their variability in oil content as well as the correlation between oil content and yield parameters. The study was carried out during the rainy season of 2015 at the Botanical garden of the Department of Biological Sciences, Plant science and Biotechnology unit farm of Nasarawa State University, Keffi. The experiment was laid out in Randomized complete block design (RCBD) with three replications. Data was collected on agronomic characters such as days to emergence, days to 50% flowering, plant height, number of leaves, stem diameter, grain yield, seed weight , number of flowers, leaf area and oil content per a hundred grams of seeds. The results from these data were analyzed using ANOVA and correlation analysis. All of the analyzed traits varied significantly (P<0.05) between varieties. The variety TG × 1989 – 45F had the highest weight per plot with a mean of 3733 while TG ×1990 – 21F had the lowest mean as 1000g. It was observed that Variety TG×1989 – 42F had the highest mean for oil content (17.0ml). Oil content showed a positive correlation with number of pods r = 0.410, weight with pods r = 0.3406, weight without pods r = 1, number of seeds per pod r =0.9162* and Grain yield r = 0.215*. Based on this study soybean varieties TG ×1989 – 45F is recommended for farmers in Keffi area interested in high grain yield and oil content, respectively.